1981
DOI: 10.1039/p29810000753
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 substituent chemical shifts in the side-chain carbons of aromatic systems: the importance of π-polarization in determining chemical shifts

Abstract: 13C Substituent chemical shifts of the carbonyl sites in the side-chains of meta-and para-substituted benzenes of the type XC,H,COZ have been measured. Analysis of this data using the dual substituent parameter method shows that inductive effects are predominant, The reverse inductive contribution observed is explained in terms of a xpolarization mechanism. Critical support for this mechanism is obtained from additional series where the carbonyl is complexed with Lewis acids. The concepts of ' extended ' and '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
85
1
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 0 publications
7
85
1
1
Order By: Relevance
“…As the phenyl substituent becomes more electron-withdrawing, forms B and C become disfavored 8 due to π-polarization. 9 The diminished delocalization increases the energy of the C i ′=O i π orbital and decreases the energy of the C i ′=O i π * orbital, making C i ′ =O i more electrophilic. The decreased delocalization is also manifested in the increased contribution from resonance form A, which results in greater double-bond character and higher C i ′=O i vibrational frequency.…”
mentioning
confidence: 99%
“…As the phenyl substituent becomes more electron-withdrawing, forms B and C become disfavored 8 due to π-polarization. 9 The diminished delocalization increases the energy of the C i ′=O i π orbital and decreases the energy of the C i ′=O i π * orbital, making C i ′ =O i more electrophilic. The decreased delocalization is also manifested in the increased contribution from resonance form A, which results in greater double-bond character and higher C i ′=O i vibrational frequency.…”
mentioning
confidence: 99%
“…2 to the data of Solaniova, et al, Brownlee, 15 They also reported the negative ρI values for β-C (-1.1) and 1-C (-0.8) and the positive ρI values for α-C (2.7) and 4-C (0.3). Although the signs of the values may be unchanged, the calculations were done with different sets of four resonance scales (σR-, σR o , σR BA , and σR+) so that the best fit could be obtained.…”
Section: Resultsmentioning
confidence: 52%
“…This is understandable because π polarization of a conjugate system induces an alternating partial positive and negative charge at each end of the π unit. 1,13 The magnitude of ρ 2-C , however, is about nine times larger than that of ρ 7a-C . This may be evidence of the conformation Ia being more favorable than Ib.…”
Section: Resultsmentioning
confidence: 96%
“…The assignments for carbons bearing a proton were quite obvious, but the carbons and the protons of the ester groups were assigned by examination of HMBC spectra. The 3a-COOCH 3 of 2 is bonded to an sp 3 -hybridized carbon atom and its 13 C chemical shift of the carbonyl carbon is downfield by about 10 ppm compared to those of 2-, 3-and 4-COOCH 3 which are bonded to an sp 2 -hybridized carbons. The methoxy carbon of 3a-COOCH 3 group is also further downfield than other ester groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation